2019
DOI: 10.1002/adma.201806538
|View full text |Cite
|
Sign up to set email alerts
|

DNA Hydrogels and Microgels for Biosensing and Biomedical Applications

Abstract: DNA hydrogels, which take advantage of the unique properties of functional DNA motifs, such as specific molecular recognition, programmable and high‐precision assembly, multifunctionality, and excellent biocompatibility, have attracted increasing research interest in the past two decades in diverse fields, especially in biosensing and biomedical applications. The responsiveness of smart DNA hydrogels to external stimuli by changing their swelling volume, crosslinking density, and optical or mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
158
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(173 citation statements)
references
References 105 publications
0
158
0
Order By: Relevance
“…[3][4][5][6] For example, the DNA hydrogel is composed of many inter-and intramolecular hybridization networks. [11,12] The dsDNA repeats are not in their perfect DNA duplex forms. Therefore, such applications are not sensitive to the potential 3′ overhang.…”
Section: A New Cost-effective Methods For the Synthesis Of High-copy Dmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] For example, the DNA hydrogel is composed of many inter-and intramolecular hybridization networks. [11,12] The dsDNA repeats are not in their perfect DNA duplex forms. Therefore, such applications are not sensitive to the potential 3′ overhang.…”
Section: A New Cost-effective Methods For the Synthesis Of High-copy Dmentioning
confidence: 99%
“…DOI: 10.1002/smll.202003671 range of applications (see review articles [11,12] ), such as delivery of drugs and genes, sensing of various signals, and as a scaffold for tissue engineering. However, one disadvantage of DNA hydrogels is their costly and complicated preparation pipeline, which could become a major obstacle for scaling up the production and applications of this material.…”
mentioning
confidence: 99%
“…Using different responsive DNA hydrogels in which enzymes, DNAzymes, or catalytic nanomaterials are entrapped, researchers have developed various colorimetric visual sensors and readout devices based on the sol-gel transition strategy for different kinds of biotargets, such as metal ions and glucose. Liu and co-workers [431] demonstrated that covalently crosslinked polyacrylamide hydrogels can be used as a platform to attach Hg 2+ -responsive DNA structures for the ultrasensitive detection and removal of Hg 2+ [432]. Shape-memory DNA hydrogels that can reversibly respond to external stimuli have also been developed.…”
Section: Biosensing Applicationsmentioning
confidence: 99%
“…In recent years scientists have proposed numerous flexible biosensors that are able to monitor substances from body fluids, e.g., representative ions or DNA molecules to retrieve the health status. [199][200][201] Stoliar et al [34] fabricated an ultrathin FET based on pentacene as the semiconducting layer to achieve the label-free sensing of DNA molecules. As shown in Figure 12a, the DNA molecules were absorbed onto the two-monolayer-thick pentacene film from a solution because of electrostatic adsorption.…”
Section: F-fet Sensors Toward Health Monitoringmentioning
confidence: 99%
“…In recent years scientists have proposed numerous flexible biosensors that are able to monitor substances from body fluids, e.g., representative ions or DNA molecules to retrieve the health status. [ 199–201 ]…”
Section: Chemical and Biological Sensors Based On F‐fetsmentioning
confidence: 99%